Determinan Motivasi Manajemen Perusahaan Dalam Melakukan Tax Planning - Anjami Nadila; Alistraja Dison Silalahi (Journal of Business and Economics Research (JBE), 2022)
This study aims to examine the effect of taxation policy, tax administration, taxpayer morale and gaps on the motivation of company management in tax planning (empirical study on food and beverage industry companies registered in the North Sumatra Disperindag). Respondents from this study were food and beverage industry companies registered in the North Sumatra Industry and Trade Department. The method of the sample method uses random sampling and the Slovin formula. The samples obtained were 77 food and beverage industry companies. The data used is primary data collected through a questionnaire. This study uses multiple regression analysis techniques for hypothesis testing and has test assumptions to ensure the feasibility of the data. The data processing used in this study uses SPPS Version 25. The results of this study indicate that tax policy, taxpayer morale and gaps have a positive and significant impact on the motivation of company management in tax planning. The results of this study also show that tax policy, taxpayer morale, and gaps have a simultaneous effect on the motivation of company management in tax planning.